PECULIARITIES OF CONNECTIVE TISSUE DEGRADATION IN RAT’S LIVER ON EARLY TERMS OF CHRONIC ALCOHOLIC HEPATITIS MODELLING - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A. (World of Medicine and Biology, 2020)
The article deals with the peculiarities of connective tissue degradation in rat liver on early terms of chronic alcoholic hepatitis modelling. Modeling of chronic alcoholic hepatitis leads to the development of oxidative stress in rat liver tissues due to a decrease in the activity of antioxidant enzymes and an increase in the production of reactive oxygen species. As a result of the development of oxidative stress in the liver of rats in the first stages of modeling alcoholic hepatitis, the concentration of the anti-inflammatory heparin-heparan fraction of glycosaminoglycans decreases, the accumulation of keratan-dermatan and chondroitin fractions of glycosaminoglycans occurs. The processes of degradation of the fibrous components of the liver’s connective tissue increase and the concentration of the sulfide anion decreases.